CO2 Emission and Trade: Distinction between Import and Export of Intermediate and Final Goods - Ali Mazyaki; Mana Shaabani Rad; Arian Daneshmand (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2022)
The main purpose of this study was to investigate the role of trade by export and import of intermediate and final goods on environmental degradation, and carbon dioxide emission, in the form of the Environmental Kuznets Curve (EKC). For this purpose, a panel data set of OECD, and non-OECD countries from 1998 to 2018 was used. According to the results, the EKC was established in all samples. In addition, while with a sample of OECD countries, trade has a beneficial or inverse effect on carbon dioxide emissions; with a sample of non-OECD countries, and that of all countries, a non-beneficial or direct effect from trade on carbon dioxide emissions prevails. Also, an important conclusion is that imports, regardless of the type of goods, had a more destructive effect on the environment than exports in all samples. Therefore, theories supporting beneficial effects of exports, e.g. improving technology, or destructive effects of imports through energy-intensive products, are better explanations of the issue than theories of destructive consumption of energy resulting from exports, or beneficial effects of imports for the environment